Type of Intercept Trap Not Important for Capturing Female Sirex noctilio and S-nigricornis (Hymenoptera: Siricidae) in North America - Haavik, Laurel J.; Batista, Elder [UNESP]; Dodds, Kevin J.; Johnson, Wood; Meeker, James R.; Scarr, Taylor A.; Allison, Jeremy D. (Entomological Soc Amer, 2014)
Current detection tools for Sirex noctilio F. (Hymenoptera: Siricidae) in North America are poor. To determine the importance of intercept trap type for capturing females of S. noctilio and its native congener, Sirex nigricornis F., in eastern North America, we report on seven trap comparison studies from different years and geographic locations. Among studies, total numbers of S. noctilio captured were low (mean of <= 1waspper trap). Total numbers of S. nigricornis caught were generally greater, andranged from ameanof 1-13 wasps per trap. Nearly all studies found no significant differencesamongintercept trap types in the number of woodwasps caught. For future studies, we recommend that either panel or 12-unit Lindgren funnel traps be used to catch S. noctilio or S. nigricornis in eastern North America.
Keywords: European woodwasp; invasive species; Lindgren funnel trap; delimitation survey